Push characteristics in wheelchair court sport sprinting - van der Slikke, R.; Berger, M.; Bregman, D.; Veeger, D. J. (Procedia Engineering, 2016)
Short sprints are important components of most wheelchair court sports, since being faster than the opponent often determines keeping ball possession or not. Sprinting capacity is best measured during a field test, allowing the athlete to freely choose push strategies adapted to their own wheelchair setting, physical ability, classification and speed changes during a sprint. The key test outcome is sprint duration, but there are various ways to accomplish the same sprint time. So can different push strategies be identified in a wheelchair sport and how do they relate to athlete level/classification and wheelchair configuration? These relationships were investigated by field tests of 30 male wheelchair basketball athletes during a 12 meter sprint in their own wheelchair. A recently developed method for ambulatory measurement was used to calculate wheelchair kinematics [1], providing outcomes on displacement, speed, acceleration and pushes. Additionally maximal isometric push force was recorded and rear seat height was noted. Within the measured athletes, internationals were expected to be faster due to a better physical training status and technique, allowing them to sprint with fewer (but more powerful) pushes. Likewise, athletes of higher classification were expected to be faster due their superior physical capacity, but the effect on the number of pushes used was not that evident. Video analysis was added to validate push detection of the ambulatory measurement system. Mutual correlations and competition level differences of sprint characteristics were calculated. General Linear Models (GLM) were drawn to determine the effect of competition level and classification on sprint time and number of pushes.